Pengaruh Komunikasi Pemasaran dan Kepercayaan Terhadap Minat Masyarakat Menggunakan Tabungan Smart IB pada PT. Bank Sumut Syariah Cabang Marelan Raya - Irma Verawati; M.Abrar Kasim Hutagalung (STIKes Ibnu Sina Ajibarang, 2025)
This research aims to determine and analyze the influence of marketing communications and trust on people's interest in using smart Ib savings at Bank Sumut Syariah Kcp Marelan Raya. The research methodology used is quantitative research using a sampling technique using a saturated sample with a total of 100 respondents. The data collection technique uses a questionnaire processed using SPSS version 26 for Windows. Data analysis uses multiple linear regression. Based on partial research results, the marketing communication variable has a positive and significant effect on people's interest in using Smart Ib savings with a calculated t value of 20,037 > 1.984 and a significant value of 0.000 < 0.05, and trust does not have a positive and significant effect on people's interest in using Smart Ib savings with a value of t count is 0.643 < 1.984 and the significant value is 0.522 > 0.05. And simultaneously it shows that the marketing communication and trust variables have a significant and positive effect on people's interest in using Smart Ib savings with a calculated f value of 205,431 > f table 2.70 and a significant value of 0.000 < 0.05